Filarial worms: a systematic review and meta-analysis of diversity in animals from Iran with emphasis on human cases. Issue 9 (6th August 2020) - Ghasemi, Ezatollah; Shamsinia, Sadegh; Taghipour, Ali; Anvari, Davood; Bahadory, Saeed; Shariatzadeh, Seyyed Ali; Kordi, Bahareh; Majidiani, Hamidreza; Borji, Hassan; Chaechi Nosrati, MohammadReza; Yousefi, Ali; Shams, Morteza
Abstract: Current systematic review and meta-analysis demonstrate the prevalence reports of filariasis in animals in Iran along with human cases. Studies were screened, relevant papers were selected and the random-effect model was used by forest plot with 95% confidence interval (CI). Of 17 records of human case-reports, particularly from Khuzestan province (5 cases), Dirofilaria repens was the most detected parasite (10 cases) with higher involvement of the right eye (7 cases) than other organs. Eleven animal species were reported to be parasitised by filarioids in Iran. The prevalence of Dirofilaria immitis in canids was 14.69% (95% CI: 10.33–19.67), with highest rates (20.92%; 95% CI: 13.84–29.03) in free-ranging dogs. Male (10.07%; 95% CI: 5.10–16.47) and more than 1-year old (20.77%; 95% CI: 8.66–36.42) dogs were more likely to be found infected. The frequency of other filarioids of zoonotic interest was: Acanthocheilonema reconditum in dogs 2.15% (95% CI: 0.71–4.33), Dipetalonema evansi in camels 10.16% (95% CI: 4.73–17.34), Onchocerca cervicalis in horses 3.63% (95% CI: 1.44–6.75%) and Onchocerca fasciata 16.57% (95% CI: 10.12–24.24%) in camels. Still, our knowledge on parasitic filariae in Iran is limited and more investigation is needed in both human and animal populations.